THE INFLUENCE OF ORGANIZATIONAL CLIMATE ON EMPLOYEE WORK EFFECTIVENESS IN THE INTEGRATED LICENSING SERVICE AGENCY OF PANDEGLANG DISTRICT - Nana Suandana, Nana Suandana (NIAGARA Scientific Journal, 2023)
As one of the government agencies serving various public interests, every SKPD in Pandeglang Regency is included in the Pandeglang Regency Integrated Licensing Service Agency. It should be enthusiastically to improve the work effectiveness of its employees, so that there are no more complaints and even strong protests from the public. Organizational climate describes the internal environment of the organization. Generally, organizational climate is very easily controlled by leaders or managers. Organizational climate is the perception of members of the organization regarding the dimensions of organizational climate that are felt directly. Thus it is believed that the working atmosphere or organizational climate greatly influences the effectiveness of an organization. The better the organizational climate, the more effective the work of an employee or organization and vice versa. If we relate it to government organizations, effective organizational performance will have a direct impact on improving services to the public/community. The main design in this study is explanatory research which focuses on testing between hypothesized variables, then aims to measure and test the causal relationship of the variables that have been determined. While the population used as respondents was 58 respondents who were employees of the Pandeglang Regency Integrated Licensing Service Agency. Based on the results of the research and discussion, it can be concluded that there is a positive and significant influence of organizational climate on work effectiveness, that through a significance test using the t test statistic, the tcount value for β1 is 6.152 and ttable with degrees of freedom with a numerator of 2 and a denominator of 56 at ɑ (0 .05) of (1.980 to 2.00). Thus tcount (6.152) > ttable (1.980 to 2.00) shows that organizational climate can increase work effectiveness at the Pandeglang Regency Integrated Licensing Services Agency.